Gene Network Mechanism of Zhilong Huoxue Tongyu Capsule in Treating Cerebral Ischemia–Reperfusion - Li, Na; Sun, Jie; Chen, Ji-Lin; Bai, Xue; Wang, Ting-Hua (Frontiers in Pharmacology, 2022)
Abstract Objective: To investigate the gene network mechanism of Zhilong Huoxue Tongyu capsule (ZLH) in the treatment of cerebral ischemia-reperfusion through network pharmacology, molecular docking validation, and animal behavioral experiments. Methods: The network pharmacology was used to search for crossover genes between ZLH and cerebral ischemia-reperfusion, and protein-protein interaction (PPI) network, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis was performed. Hub genes were screened according to Degree value, molecular docking verification was performed by Aoutdock Vina software, and animal behavior experiment was conducted at last. Results: There were 126 intersecting genes between ZLH and cerebral ischemia-reperfusion, where the most important biological process was response to lipopolysaccharide, the most important cell component was raft, and the most important molecular function was cytokine receptor binding. The most important KEGG signaling pathway was age-rage signaling pathway in diabetic complications. According to the string interaction in PPI network, 10 Hub genes were screened by Degree value in Cytoscape for molecular docking verification with drugs. Among them, the target proteins in ESR1-Guizhi and RELA -Guizhi were not docked with drug ligands, and other drugs and proteins could form stable molecular binding patterns. According to the relationship diagram of cerebral ischemia-reperfusion - ZLH -KEGG pathway, it can be seen that multiple genes have regulatory interactions on cerebral ischemia-reperfusion. In addition, the behavioral experiment results showed that the neurological function of rats in the NS group was significantly higher than that in the sham group after 5 days of treatment with ZLH at high doses. After the treatment, the neurological function of rats in the ZLH group was significantly higher than that in the NS group (P=0.000). Conclusion: Zhilong Huoxue Tongyu capsule improve the cerebral ischemia-reperfusion.